Применение комбинированных голографических интерферограмм к исследованию неустановившихся деформаций - Селиванов, Ю.М. (Видавничий дім "Академперіодика" НАН України, 2007)
An approach to the investigation of nonstationary deformations for an inhomogeneous shell with utilization of the holographic time-average method for the preliminary exposure of a static state is proposed.